Plant Biology: Journey to the Center of the Casparian Strip - Stöckle, Dorothee; Vermeer, Joop (My University, 2020)
Diffusion barriers in roots play an important role in regulating the movement of compounds between the soil environment and the vasculature. A new study provides new mechanistic insights into how a pair of copperbinding proteins facilitate the formation of a ligniﬁed nanodomain within Casparian strips.